Experimental study on rectangular CFT columns with different steel grades and thicknesses. (March 2017) - Choi, In-Rak; Chung, Kyung-Soo; Kim, Chang-Soo
Abstract: To investigate the structural behavior of rectangular concrete-filled steel tube columns with different steel grades (high-strength steel HSA800 and mild steel SM490) and thicknesses (25 mm and 8 mm) in flanges and webs (i.e., hybrid RCFT sections) under weak axis bending, eccentric axial load tests were performed for four column specimens. Test parameters included the strength of steel flanges, strength of core concrete, and filling of core concrete. To verify the welding procedure and soundness of welded joints between the different grade steel plates, qualification tests were also conducted. The test results were compared with the predictions by current design codes and nonlinear numerical analysis, and to supplement the test results, numerical parametric study was performed. The experimental and numerical investigations showed that thick flanges of high-strength steel, thin webs of mild steel, and electrodes for the thin and mild steel can be used to increase cost efficiency without performance degradation and the hybrid RCFT sections can develop the full plastic strength. Highlights: Experimental investigation on rectangular CFT columns with different steel grades and thicknesses (hybrid RCFT columns) Numerical investigation on hybrid RCFT columns with various design parameters Verification of welding procedure and soundness of welded joints between different grade steel plates Evaluation of applicability of current design codes to hybrid RCFT columns